2020
DOI: 10.1021/acsami.0c06032
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a Novel Biosensor Based on the Self-assembly of Dual-Enzyme Cascade Amplification-Induced Copper Nanoparticles for Ultrasensitive Detection of MicroRNA153

Abstract: MicroRNAs (miRNAs) have received extensive attention because of their potential as biomarkers for cancer diagnosis and monitoring, and their effective detection is very significant. Here, a specific, one-pot, rapid, femtomolar sensitive miRNAs detection biosensor was developed based on the target-triggered three-way junction (3-WJ) and terminal deoxynucleotide transferase (TDT)/Nt.BspQI in combination with activated copper nanoparticles (CuNPs) self-assembly. To this end, a 3-WJ hairpin probe and helper probe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…The characteristic of copper nanoclusters (CuNCs) to produce red fluorescence under ultraviolet (UV) radiation has attracted wide attention and applications of scientists in biosensor design [ 11 , 12 ]. Ligands such as nucleic acids [ 13 ], cysteine [ 14 , 15 ], and bovine serum albumin [ 16 , 17 ] can generate CuNCs in the presence of reducing agents.…”
Section: Introductionmentioning
confidence: 99%
“…The characteristic of copper nanoclusters (CuNCs) to produce red fluorescence under ultraviolet (UV) radiation has attracted wide attention and applications of scientists in biosensor design [ 11 , 12 ]. Ligands such as nucleic acids [ 13 ], cysteine [ 14 , 15 ], and bovine serum albumin [ 16 , 17 ] can generate CuNCs in the presence of reducing agents.…”
Section: Introductionmentioning
confidence: 99%
“…Nanotechnology, with the improvement and application of the nano‐particles (NPs)/nanocarriers with dimension in the nanoscale range (1 ~ 100 nm) (Gong et al, 2018; Piao et al, 2019; B. Zhang, Gao, et al, 2018), has been widely utilized in a variety of fields, including medicine (Emerich & Thanos, 2003), pharmacy (Li et al, 2020), biological detection (Chen et al, 2020; J. Cui et al, 2020; Peng, Huang, et al, 2020), optics (Ochmann et al, 2017; Peng, Qin, et al, 2020), and agriculture (Curtis & Wilkinson, 2001; Prasad et al, 2017). The extremely small size of NPs allows efficient entrance into living system such as animal and human body.…”
Section: Introductionmentioning
confidence: 99%
“…T junctions (also called three-way junctions) that formed of three strands of DNA rely on the Watson–Crick complementary base pairing principle and are a type of stable architecture with demonstrated versatility in the biosensing field. , Cheng et al reported a kind of defective T junction that contained an artificial vacuole at the junction site and was more conformationally stable than the traditional T junction . To overcome the shortcomings of the normal SDA strategy, herein, through the ingenious design of a pair of dual-function probes, a new SDA method in which the defective T junction structure is first used to support SDA (dT-SDA) is proposed.…”
Section: Introductionmentioning
confidence: 99%